The Palgrave Handbook of Twentieth and Twenty-First Century Literature and Science
XXIX, 689 p. 31 illus., 25 illus. in color.
Keywords: This handbook illustrates the evolution of literature and science, in collaboration and contestation, across the twentieth and twenty-first centuries. The essays it gathers question the charged rhetoric that pits science against the humanities while also demonstrating the ways in which the convergence of literary and scientific approaches strengthens cultural analyses of colonialism, race, sex, labor, state formation, and environmental destruction. The broad scope of this collection explores the shifting relations between literature and science that have shaped our own cultural moment, sometimes in ways that create a problematic hierarchy of knowledge and other times in ways that encourage fruitful interdisciplinary investigations, innovative modes of knowledge production, and politically charged calls for social justice. Across units focused on epistemologies, techniques and methods, ethics and politics, and forms and genres, the chapters address problems ranging across epidemiology and global health, genomics and biotechnology, environmental and energy sciences, behaviorism and psychology, physics, and computational and surveillance technologies. Chapter 19 is available open access under a Creative Commons Attribution 4.0 International License via link.springer.com.